2019
DOI: 10.5603/arm.2019.0018
|View full text |Cite
|
Sign up to set email alerts
|

CT Imaging Features of Thin-Walled Cavitary Squamous Cell Lung Cancer

Abstract: Primary lung cancer manifesting as a thin-walled solitary cavity, occurs relatively infrequently. The most common histologic type presenting such a pattern is squamous cell cancer, followed by adenocarcinoma, and finally-large cell cancer. Cavitation is typically not seen in small cell lung cancer. Entities indicating malignancy of such lesions include irregular cystic wall, wall nodule formation, nodular septa or increased standard uptake on positron emission tomography (PET). We are presenting a case of a sq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
0
6
1
Order By: Relevance
“…Although cavities are commonly seen in lung cancer patients, accounting for 22% of all primary lung carcinomas (9), thin-walled cystic lung cancer has been rarely reported in the literature. Cavitary lung cancer is common in patients with squamous cell carcinoma (SCC) and is often seen in adenocarcinomas (10). Occasionally, it can be found in bronchioloalveolar carcinoma (BAC), while small-cell lung cancer has not been associated with cavitary lesions (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although cavities are commonly seen in lung cancer patients, accounting for 22% of all primary lung carcinomas (9), thin-walled cystic lung cancer has been rarely reported in the literature. Cavitary lung cancer is common in patients with squamous cell carcinoma (SCC) and is often seen in adenocarcinomas (10). Occasionally, it can be found in bronchioloalveolar carcinoma (BAC), while small-cell lung cancer has not been associated with cavitary lesions (10).…”
Section: Discussionmentioning
confidence: 99%
“…Cavitary lung cancer is common in patients with squamous cell carcinoma (SCC) and is often seen in adenocarcinomas (10). Occasionally, it can be found in bronchioloalveolar carcinoma (BAC), while small-cell lung cancer has not been associated with cavitary lesions (10).…”
Section: Discussionmentioning
confidence: 99%
“…As LCCA has an overall low prevalence, it is easy for radiologists and respiratory doctors to miss it [ 8 ]. Patients with LCCA tend to have a worse prognosis than those with non-cystic airspaces lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Nodular opacities in the course of M. szulgai infection occur less frequently; nevertheless, both forms can be suspected for malignancy [ 12 ]. Opoka et al reported a rare case of squamous lung cancer manifested by thickening wall of cavity, which was previously stable during a two year follow-up period [ 14 ]. In our case, coexistence of NTM infection and breast cancer lung metastasis as well as primary lung cancer had been suspected.…”
Section: Discussionmentioning
confidence: 99%